2020
DOI: 10.1111/een.12912
|View full text |Cite
|
Sign up to set email alerts
|

Metacommunity structure analysis reveals nested patterns in deconstructed macroinvertebrates assemblages

Abstract: 1. Understanding processes driving patterns of species distribution and diversity is one of the main objectives of community ecology. 2. The aim of our study was to evaluate the spatial variation in assemblage composition of stream-dwelling macroinvertebrates and identify which factors (e.g. water quality, land cover) are the most important drivers. 3. We applied the elements of the metacommunity structure approach on a dataset of 38 communities from the Futaleufú basin in northwestern Patagonia. To better und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 84 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…This may blur the observed metacommunity patterns. Therefore, dividing entire metacommunities into more homogeneous deconstructed trait groups and, respectively, examining their typologies and underlying drivers may have the potential to provide clues to differences among different seasons (Fernandes et al, 2014; Tonkin et al, 2016; Williams‐Subiza et al, 2020). Finally, the dominant macroinvertebrate taxa in this drainage basin are characterized by small body size, short life span, fast development and high dispersal capability (Li et al, 2019), which may thus display relatively high resistance and resilience to natural and anthropogenic disturbances (Kuzmanovic et al, 2017; Lytle & Poff, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may blur the observed metacommunity patterns. Therefore, dividing entire metacommunities into more homogeneous deconstructed trait groups and, respectively, examining their typologies and underlying drivers may have the potential to provide clues to differences among different seasons (Fernandes et al, 2014; Tonkin et al, 2016; Williams‐Subiza et al, 2020). Finally, the dominant macroinvertebrate taxa in this drainage basin are characterized by small body size, short life span, fast development and high dispersal capability (Li et al, 2019), which may thus display relatively high resistance and resilience to natural and anthropogenic disturbances (Kuzmanovic et al, 2017; Lytle & Poff, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of recent studies in rivers have evaluated metacommunity structures and assembly mechanisms in different habitats (Heino, Soininen, et al, 2015; Tonkin et al, 2016), network positions (López‐Delgado et al, 2019; Tonkin et al, 2015), catchments (Alves‐Martins et al, 2019; Tonkin, Shah, et al, 2017), ecoregions (Brasil et al, 2017; Murray‐Stoker & Murray‐Stoker, 2020), as well as among multiple biological groups (He et al, 2020; Williams‐Subiza et al, 2020). Generally, these studies found that environmental filtering frequently has greater importance than spatial effects on community structure, and a metacommunity thus usually displays a gradient‐driven typology (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The system is perfectly nested if all species in the small island are also found in the adjacent larger island; however, this perfectly nested pattern rarely occurs in nature (Wright et al., 1998 ). Nestedness, to some extent, is one of the most frequently occurring patterns for biotas in the island landscape (Wang et al., 2013 ; Wright et al., 1998 ), including birds (Fernández‐Juricic and Jokimäki, 2001 ; Murgui, 2010 ; Wang et al., 2013 ), fish (Fernández‐Juricic and Jokimäki, 2001 ), insects (Fernández‐Juricic, 2002 ; Fernández‐Juricic and Jokimäki, 2001 ; Xu et al., 2017 ), plants (Platt and Lill, 2006 ), mammals (Chen et al., 2019 ), reptiles (Wang et al., 2010 ), and macroinvertebrates (Florencio et al., 2011 ; Williams‐Subiza et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%